A short guide to long-run time-phased systems of production (2008)
The paper discusses brietly several long-run systems of production vis-a-vis alternative theories of value and distribution stated by Marx, classical-neoricardian, post-Leontief-neoclassical, and post-Keynes-Srafra authors during the last hundred and fifty years. All the systems of production considered in thepaper have in common the circular production of commodities by means of commodities. A distinctive characteristic of these systems is the standard of valuein terms of which the wage rate and the prices of commodities are expressed. Inparticular, the logical structure of the systems of prices of production implies that different standards of value imply different theories of value and distribution both real and monetary in character. Methodological pluralism suggests that distinct theories of value and distribution reflect different scientific normative economic paradigms. It appears that dialectics is needed in order to trascendinter-paradigmatic debate.